Uso da rastreabilidade de instrumental cirúrgico em Centro de Materiais Estéreis (CME) - Walravens, Juliana Almeida de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Introdução: O Centro de Material e Esterilização (CME) é destaque no contexto de organizações de saúde e consiste em unidade de apoio a todos os serviços assistenciais e diagnósticos, os quais utilizam artigos odonto-médico-hospitalares na prestação de assistência aos usuários. Por sua complexidade se faz necessário o gerenciamento adequado dos materiais e equipamentos, sendo uma das atividades a rastreabilidade de materiais com por exemplo os instrumentais cirúrgicos. Objetivo: O presente trabalho visa elaborar parecer técnico-científico (PTC) para avaliar o uso do sistema de rastreabilidade informatizada de instrumental cirúrgico em Centro de Materiais Estéreis (CME) e procedimento operacional padrão (POP) para identificação de instrumentais cirúrgicos por fita adesiva. Método: Tratade um estudo de revisão de literatura, utilizando bases de dados como Medline via Pubmed, Lilacs, Embase, Google Acadêmico e Cochrane. Resultados: Foram elaborados dois produtos, ou seja, parecer técnico científico (PTC), segundo as Diretrizes Metodológicas do Ministério da Saúde e um protocolo operacional padrão (POP) para rastreabilidade com fita adesiva. Conclusão: Com presente trabalho pode-se concluir a importância da elaboração de um PTC, contribuindo para tomada de decisão do gestor frente a incorporação de novas tecnologias bem com utilização de POP no serviço para garantir padronização dos procedimentos executados e maior segurança do paciente.

Introduction: The Material Sterilization Center (CME) is highlighted in the context of health organizations and is characterized as support units for all assistance and diagnostic services. Due to its complexity, the manager needs to have adequate control of the materials and equipment. Among this control, the traceability of materials such as surgical instruments stands out. Two types of traceability are found in the literature, such as logistical traceability, which is guided in providing information, in article locations, determining its origin and destinations ; qualitative traceability, which provides information on faults and their causes, identification of the source with quality deviations and ascertaining who is responsible.Objective: This study aims to evaluate the effectiveness of surgical instrument traceability in a Sterile Materials Center (CME) through a technical-scientific opinion and to develop a standard operating procedure (SOP) for identifying surgical instruments using adhesive tape.. Method: It is a literature review study. A scientific technical opinion (PTC) was elaborated, according to the Methodological Guidelines of the Ministry of Health and a standard operational protocol (SOP) for traceability with adhesive tape.Results:The search strategy resulted in obtaining 1,036 articles that were selected and screened according to the inclusion criteria. 645 articles were obtained from Pubmed, 142 from Cochrane, 57 from Lilacs, 37 manuscripts from Embase and 155 from Google Scholar. As for the searches in the ATS databases, no database reported material related to the theme. The screening and selection of studies according to the eligibility criteria resulted in the inclusion of 5 studies. Conclusion: With this work, it can be concluded the importance of elaborating a PTC , contributing to the manager's decision-making regarding the incorporation of new technologies as well as the use of POP in the service to ensure standardization of the procedures performed and greater patient and patient safety.
Use of traceability of surgical instruments in a Sterile Materials Center (SMC)
Keywords: Esterilização; Centro de Esterilização; Informática em enfermagem; Sistemas de informação em salas cirúrgicas; Sterilization; Sterilization Center; Information systems in surgical rooms; Informatics in nursing